A Cross-Sectional Study Of Physical Fitness Index By Using Modified Harvard Step Test In Taekwondo Athletes - Patil, Neha Netaji; shinde, Smrutika v (Journal of Neonatal Surgery, 2025)
Background: Taekwondo is known for its unique rapid, high, and spinning kicks. The sport's movement patterns are thought to be quite taxing on the majority of participants' muscle groups. It is believed that the most significant element influencing athletic performance is physical fitness. physical fitness is the capacity to exercise for extended periods of time. Growing physical fitness is getting greater attention as a result of the rising popularity of martial arts among youth and their desire to enhance their own performances. The importance of physical fitness has been discussed throughout human history, especially in the Vedas. However, exercise physiology is a relatively new topic with room for more study. Method: In this cross-sectional study, seventy five participants with mean age 21.35 (± 2.55) Taekwondo Athletes were included. They were assessed for physical fitness by using modified Harvard step test and Physical Fitness Index. Result: It was observed that from total 75 participants 39 were male i.e; 52% and 36 were female I.e; 48%. So statistically the ratio of gender distribution is almost equal. It was seen that out of total 75 participants the mean age of participants was 21.35 (± 2.55). According to study the mean value of years of practice is 4.26 (± 2.34) of all 75 participants. And mean value of hours of practice is 1.73 (± 0.45). However, it describes that these figures shed light on the individuals, overall traits, including their degrees of experience and fitness. Male and female fitness index scores do not differ significantly, according to the p-value (0.5918), indicating that gender has no bearing on physical fitness levels in this sample. Conclusion: According to the study's findings, physical fitness levels are mostly determined by factors such as age, years of practice, and practice hours. Although men perform somewhat better than women in the "Good" fitness category, the differences are not statistically significant, suggesting that gender is not a significant factor in fitness on its own. In order to improve general physical health, the study emphasises the significance of regular exercise, equitable opportunities, and organised fitness programs. To learn more about what makes people as fit as possible, future studies might look into other aspects including nutrition, lifestyle choices, and certain forms of exercise